Evaluation of PFAS treatment technology: Alkaline ozonation. Issue 3 (9th June 2020) - Thomas, Ryan; Jenkins, Kristen; Landale, Beth; Trigger, Grant; Holsen, Thomas M.; Dore, Sophia; Pope, Donald; Wasielewski, Jennifer
Abstract: A bench‐scale treatability study was performed to evaluate the effectiveness of alkaline ozonation on removing per‐ and polyfluoroalkyl substances (PFAS) present in groundwater at a former industrial site in Michigan. The study involved testing the PFAS‐impacted groundwater under alkaline ozonating conditions under a range of experimental conditions, including modifying pH, hydrogen peroxide‐to‐ozone molar ratio doses, length of ozonation pretreatment times, and sampling techniques. PFAS‐spiked samples were used to determine if inorganic ions such as fluoride (F − ), sulfate (SO4 2− ), formate (HCOO − ), acetate (CH3 COO − ), and trifluoroacetate (CF3 COO − ) were generated or if there were decreases in total organic fluorine resulting from PFAS treatment. The results from all tests indicate that decreases in PFAS concentrations were due to a combination of removal and destructive mechanisms with enhanced removal under acidic pH ozonation pretreatment conditions. Short‐chain PFAS concentrations increased during the experiments followed by an overall decrease in concentration under continuous alkaline ozonation conditions. Reductions in concentrations in perfluorooctane sulfonic acid of 75–97% were observed. Reductions in concentrations were also observed in other PFAS such as 6:2 FTS, PFHxS, PFOA, and PFNA. To our best knowledge, this is the first time that alkaline ozonation has been performed on PFAS‐impacted water while monitoring a larger suite of PFAS analytes in addition to destruction byproducts. Treatment of PFAS under the conditions discussed in this paper suggests that alkaline ozonation may be a viable remediation option for PFAS‐impacted waters.